Analysis of Student Perceptions of the Teaching Methodsof Lecturers in the Economic Education Study Program and Student Learning Motivation - Sinurat, Putri Alisa (International Journal of Students Education, 2025)
This study aims to maximize student motivation and learning outcomes and improve lecturers' teaching abilities. The approach used in this study is a qualitative approach. The method used to research on natural object conditions, where the researcher is the key instrument, data collection techniques are carried out by triangulation (combination), data analysis is inductive, and qualitative research results emphasize meaning rather than generalization. The data source in this study was fifth semester students majoring in social sciences education, accounting economics education study program. In the study, the population was fifth semester (five) economics study program students, totaling 80 people. The results of this study are students' perceptions of the teaching methods of lecturers in the economics education study program are very good and can be accepted by most students. Student learning motivation in lecture activities or learning processes is relatively high, students show good attitudes or beliefs, students show good drive or enthusiasm for learning and students always carry out strategies to obtain maximum results. The learning outcomes of students in the accounting economics education study program are relatively high and this is greatly influenced by the teaching methods of lecturers and student learning motivation.